Empiricist devotions : science, religion, and poetry in early eighteenth-century England - Smith, Courtney Weiss (Winner of the Walker Cowen Memorial Prize for an outstanding work of scholarship in eighteenth-century studies, 2016)
Featuring a moment in late seventeenth- and early eighteenth-century England before the disciplinary divisions that we inherit today were established, Empiricist Devotionsrecovers a kind of empiricist thinking in which the techniques and emphases of science, religion, and literature combined and cooperated. This brand of empiricism was committed to particularized scrutiny and epistemological modesty. It was Protestant in its enabling premises and meditative practices. It earnestly affirmed that figurative language provided crucial tools for interpreting the divinely written world. Smith recovers this empiricism in Robert Boyle's analogies, Isaac Newton's metaphors, John Locke's narratives, Joseph Addison's personifications, Daniel Defoe's diction, John Gay's periphrases, and Alexander Pope's descriptive particulars. She thereby demonstrates that "literary" language played a key role in shaping and giving voice to the concerns of eighteenth-century science and religion alike.--Provided by publisher